PENGARUH BUDAYA ORGANISASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT BPR KARYA PRIMA SENTOSA DI TANGERANG - Safiih, Abdul Rahman; Alamsyah, Agung (Journal of Research and Publication Innovation, 2024)
The purpose of this study was to determine the effect of Organizational Culture on Employee Performance, to determine the effect of Work Discipline on Employee Performance and to determine the effect of Organizational Culture and Work Discipline on Employee Performance at PT BPR Karya Prima Sentosa Tangerang. This research method uses a quantitative description method, data collection techniques using a questionnaire. The population amounted to 63 employees, the sampling used was a saturated sample technique totaling 63 employees... Data analysis using descriptive statistics, validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, simple linear regression analysis, multiple linear regression analysis, correlation coefficient analysis, determination coefficient analysis, t test and f test. The results showed that: There is an influence between organizational culture on employee performance at PT BPR Karya Prima Sentosa Tangerang, this can be proven from the simple linear regression equation Y = 11.648 + 0.643X1 and the tcount value of 5.650> t table 1.670 with a significant 0.000 <0.05. There is an influence between work discipline on employee performance at PT BPR Karya Prima Sentosa Tangerang, this can be proven from the simple linear regression equation Y = 16.339 + 0.566X2 and the tcount value of 4.415> t table 1.670 with a significant 0.000 <0.05. There is a simultaneous influence of organizational culture and work discipline on employee performance at PT BPR Karya Prima Sentosa Tangerang, this can be proven from the multiple linear regression equation Y = 3.764 + 0.507 + 0.348, the correlation coefficient value of 0.586 and 0.492, the coefficient of determination of 0.400 or 40%, and the fcount value of 21.691> ftabel 3.150 with a significant level of 0.000 <0.05.